Cictp 2014 2014
DOI: 10.1061/9780784413623.078
|View full text |Cite
|
Sign up to set email alerts
|

Location-Routing Optimization of Cold Chain Distribution Center Based on Hybrid Genetic Algorithm - Tabu Search

Abstract: Since location and route problems are of equal importance to the cold chain logistics, it is necessary to consider the location and route optimization comprehensively for the benefit of the overall system. In this paper, an optimal location-routing model considered temperature variation among sensitive products for cold chain distribution centers is designed, with the objective function to minimize the overall expenses. As a solution method, a hybrid genetic algorithm-tabu search is proposed, which is applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…The results demonstrated that the hybrid algorithm surpassed the solution efficiency of each algorithm. Zheng et al [37] addressed the temperature variation in the cold chain by using a location-routing problem to optimize the overall expanses. A hybrid version of genetic algorithm and tabu search was used with an efficient encoding scheme.…”
Section: Solution Approaches Towards the Analysis Of Cold Chainsmentioning
confidence: 99%
“…The results demonstrated that the hybrid algorithm surpassed the solution efficiency of each algorithm. Zheng et al [37] addressed the temperature variation in the cold chain by using a location-routing problem to optimize the overall expanses. A hybrid version of genetic algorithm and tabu search was used with an efficient encoding scheme.…”
Section: Solution Approaches Towards the Analysis Of Cold Chainsmentioning
confidence: 99%
“…[45][46][47][48][49] based on VRP and Refs. [50,51] based on LRP, which are the latest papers after 2013, and the earlier works can be seen in the paper of Wang et al (2018) [42].…”
Section: Cold Chain Logisticsmentioning
confidence: 99%
“…A new discrete particle swarm optimization is introduced to solve the integrated model. Zheng Guohua et al [ 20 ] proposed an optimal location–routing model considering temperature variation among sensitive products for cold chain distribution centers, and, as a solution method, a hybrid genetic algorithm-tabu search was proposed. Shi Zhao and Fu Zhuo [ 21 ] designed a satisfaction degree function according to service time windows and established the simulation model under time-dependent, and introduced the minimum envelope clustering analysis method and tabu search algorithm to solve the problem.…”
Section: Literature Reviewmentioning
confidence: 99%